Palestine, or, the Holy Land: From the Earliest Period to the Present Time - Russell, Michael, 1781-1848 (Salt Lake City, UT : Project Gutenberg, 2005)
"Palestine, or, the Holy Land: From the Earliest Period to the Present Time" by the Rev. Michael Russell, LL.D. is a historical account written in the early 19th century. The book offers a thorough exploration of the history, customs, and geography of Palestine, from its ancient foundations up to contemporary times. It aims to provide readers with an integrated view that combines a narrative of the Jewish people's history with descriptions of the land's significant religious and cultural heritage. The opening of the book presents Russell's rationale behind the dual focus on history and topography. He discusses the challenges historians face in conveying the rich historical significance of Palestine, especially in relation to the Jewish people's enduring connection to their promised land. Russell outlines his intentions to cover the social, political, and cultural aspects of the Hebrew commonwealth and emphasizes the importance of Palestine both in religious and secular contexts. He touches on key themes such as the growth and struggles of the Jewish people, their spiritual significance, and the natural beauty and geographic diversity of the Holy Land, setting the stage for a detailed exploration of its historical trajectory. (This is an automatically generated summary.)
Release date is 2005-09-01
Produced by Distributed Proofreaders
Keywords: Palestine -- Description and travel; Palestine -- History